THE INFLUENCE OF REVIEWS AND TIKTOK INFLUENCER CREDIBILITY ON PURCHASE DECISIONS FOR BITTERSWEET BY NAJLA WITH EXPECTATIONS AS A MEDIATING VARIABLE - Caecillia Hartatdji; Clarensia Sharlyn Wijaya; J.E Sutanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study aims to analyze the influence of influencer reviews and influencer credibility on purchase decisions for Bittersweet by Najla products, with consumer expectations as a mediating variable. This study employs a quantitative approach using Google Forms as the data collection instrument, with a causal-explanatory research design to analyze the relationships among variables. The data were distributed to active TikTok users in Indonesia who had watched influencer reviews of Bittersweet by Najla products and had either purchased or had the intention to purchase the products. A total of 336 valid respondents were obtained through purposive sampling. The analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method through SmartPLS version 4. The findings indicate that influencer reviews and influencer credibility significantly affect consumer expectations. Both variables are also proven to influence consumer purchase decisions both directly and indirectly through consumer expectations as a mediating variable. The results suggest that marketing strategies involving influencers can enhance consumer expectations and purchase decisions for Bittersweet by Najla products. This study also contributes to the influencer marketing literature by highlighting the role of consumer expectations as a mediating factor in digital marketing strategies, particularly in the food and beverage industry through the TikTok platform. This research is also related to Sustainable Development Goals (SDGs) 8, particularly in the aspect of economic growth. The utilization of digital marketing through influencers is considered capable of encouraging increased purchasing activities while supporting business growth in the current digital economy era.